The relation between the perception of organizational support and communication skills of sports service business employees - Pekel, Aydın; Atasoy, Taner (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The aim of this study is to evaluate the relationship between the perception of organizational support and communication skills of sports service business employees. The study group of the research consists of volunteer individuals working (n = 274) working in private sports enterprises (manager, coordinator, trainer / trainer) in Istanbul Province. The data were collected online by using the questionnaire technique. Organizational support scale and communication skill scale, perceived as data collection tools, were used. Correlation and regression analysis were used as statistical process. As a result, it is seen that the employees of the sports service business have moderate executive support and also show a good communication skills. While there was a weak, medium, and high positive relationship between the perception of organizational support and communication skills, it was determined that perceived organizational support was a predictor of communication skill.